Capitalisme d’État ou société bureaucratique de développement - Elsenhans, Hartmut (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1982)
Increasingly, one can observe the power of the state extending into the modem sector of Third World economies. Different types of cooperative relationships are established with multinational corporations, even to the point of excluding them altogether. A considerable part of the literature suggests that in this instance there is the formation of dependent capitalist societies, what could be referred to as state capitalism. Such a definition is contradictory and conceals the true operation of these societies. In fact, was are witnessing the emergence of a new type of production that the author refers to as bureaucratic development societies dominated by bureaucratically organized state classes. These state-classes collectively appropriate the social surplus and determine its allocation on a political basis allocating it either to consumption by the dominant class or to investment, but in this latter case, without consideration as to the immediate return on possible investments. The means by which such a class arrives at decisions are of particular interest because the author shows that they constitute both a hope and a threat for the broad-based development of the economies and the societies of the Third World.